Understanding dual career views of European university athletes: The more than gold project focus groups - Capranica, Laura (2022)
Previous studies have found that student-athletes (S-As) have difficulties in achieving dual career (DC) success. However, no studies have analysed the opinion of the S-As on the functioning of DC with a qualitative methodology. The aim of the present work was to collect the opinions of elite university S-As in relation to DC policy adopted by their academic institutions in different European countries. In total, 77 athletes (F = 35, M = 42; age range: 20-25 years) participated in 15 national face-to-face focus groups in five different countries, to discuss aspects that higher education institutes should implement in relation to: 1) the athletes' needs; 2) assistance/tutorship: 2) curricula requirements; 3) financial support; 4) logistic support; 5) social support; and 6) dual career policies. Fifty of the athletes competed in individual sports and twenty-seven team sports. Of them, 57 was enrolled at undergraduate, 17 was enrolled in a master and 3 in a PhD. The athletes were presented with 13 open-ended questions one by one, and were ensured freedom to interact. All the discussions were recorded. After this, a general discussion took place in which the participants identified and agreed on a final list of statements from their focus group deemed to be relevant to DC athletes as university students. Then, at a consensus meeting, the findings were combined, repetitions were eliminated, and fragmented statements were condensed into broader ones. A final list of 31 statements, organized in six related content units, were identified in relation to the athletes' needs (n = 5), assistance/tutorship (n = 5), curricula requirements (n = 4), financial support (n = 4), logistic support (n = 4), social support (n = 6), and DC policies (n = 3), respectively. In conclusion, this cross-national qualitative research study synthesized the S-As views about their needs and the most relevant DC policies and provisions that higher education institutes should provide to ensure them with positive academic experiences towards the achievement of a degree.